NVivo Software Training for Young Researchers: Pelatihan Software NVivo Kepada Peneliti Muda - Fitridawati Soehardi; Lusi Dwi Putri; Marta Dinata (Mattawang: Jurnal Pengabdian Masyarakat, 2021)
In the scope of engineering research, most of the problems are quantitative, qualitative problems are not so dominant but have a big influence on the results obtained. This qualitative research is conducted on natural objects that develop as they are, are not manipulated by researchers and the presence of researchers does not really affect the dynamics of these objects. Not all young technical researchers understand this method of qualitative data analysis. To answer this, it is necessary to provide qualitative data analysis to young researchers through Nvivo training activities, with implementation stages in the form of training in the theory and application of Nvivo as well as practicing data analysis with NVIVO. This program is used to analyze unstructured or semi-structured data such as the results of interviews, surveys, field notes, web and journal articles. The target to be achieved is community empowerment services, scientific reports and articles (journals / proceedings). The method used is learning in class lectures, discussion and question and answer as well as practice / application simulation. The results obtained are partners understand how to use the NVivo application, out of 25 (twenty five) participants with a 'Very Good' score of 12%, a 'Good' score of 60% a 'Medium' score of 28% and a 'Not Appearing' value of 0%. The conclusion obtained is the increased capacity of partners in using the Nvivo application. Abstrak Dalam lingkup penelitian bidang teknik sebagian besar permasalahannya bersifat kuantitatif, permasalahan yang bersifat kualitatif tidak begitu dominan namun memberi pengaruh besar pada hasil yang diperoleh. Penelitian kualitatif ini dilakukan pada objek alamiah yang berkembang apa adanya, tidak dimanipulasi oleh peneliti dan kehadiran peneliti tidak begitu mempengaruhi dinamika pada obyek tersebut. Tidak semua peneliti muda bidang teknik memahami metode analisis data kualitatif ini. Untuk menjawab hal tersebut maka perlu diadakan pembekalan mengenai analisis data kualitatif kepada para peneliti muda melalui kegiatan pelatihan Nvivo, dengan tahapan pelaksanaan berupa pelatihan teori dan aplikasi Nvivo serta praktik analisis data dengan Nvivo. Program ini digunakan untuk menganalisis data tidak terstruktur atau semi terstruktur seperti hasil interview, survey, catatan lapangan, web dan artikel jurnal. Target yang ingin dicapai adalah jasa pemberdayaan masyarakat, laporan dan artikel ilmiah (jurnal/prosiding). Metode yang digunakan adalah pembelajaran di kelas ceramah, diskusi dan tanya jawab serta praktik/simulasi aplikasi. Hasil yang diperoleh adalah mitra memahami cara menggunakan aplikasi NVivo, dari 25 (dua puluh lima) orang peserta dengan nilai ‘Sangat Baik’ sebesar 12%, nilai ‘Baik’ sebesar 60% nilai ‘Sedang’ 28% dan nilai ‘Tidak Tampil’ sebesar 0%. Kesimpulan yang diperoleh adalah meningkatnya kapasitas mitra dalam menggunakan aplikasi Nvivo.